2019
DOI: 10.1002/ece3.5192
|View full text |Cite
|
Sign up to set email alerts
|

Transstadial immune activation in a mosquito: Adults that emerge from infected larvae have stronger antibacterial activity in their hemocoel yet increased susceptibility to malaria infection

Abstract: Larval and adult mosquitoes mount immune responses against pathogens that invade their hemocoel. Although it has been suggested that a correlation exists between immune processes across insect life stages, the influence that an infection in the hemocoel of a larva has on the immune system of the eclosed adult remains unknown. Here, we used Anopheles gambiae to test whether a larval infection influences the adult response to a subsequent bacterial or malaria parasite infection. We found that for both female and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 81 publications
0
24
0
2
Order By: Relevance
“…Tidbury et al 13 determined that 8 day-old Plodia interpunctella larvae, primed with a low dose of P. interpunctella granulosis virus, could survive a lethal virus challenge in the adult stage. Likewise, Brown et al 16 observed that Anopheles gambie adult mosquitoes from infected larvae have stronger antibacterial activity in their hemocoel. They also showed increased susceptibility to malaria infection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tidbury et al 13 determined that 8 day-old Plodia interpunctella larvae, primed with a low dose of P. interpunctella granulosis virus, could survive a lethal virus challenge in the adult stage. Likewise, Brown et al 16 observed that Anopheles gambie adult mosquitoes from infected larvae have stronger antibacterial activity in their hemocoel. They also showed increased susceptibility to malaria infection.…”
Section: Discussionmentioning
confidence: 98%
“…development stages in insects [11][12][13][14][15][16] . On the other hand, it has been suggested that Ae.…”
mentioning
confidence: 99%
“…In the present study, we uncovered that mosquitoes that receive two infections have more hemocytes available to quell the infection than mosquitoes that experience a single infection. Studies on E. coli -infected adult A. gambiae have documented an infection-induced increase in the number of hemocytes [ 35 , 37 , 44 , 45 ], and this increase extends to when mosquitoes acquire the E. coli infection during the larval stage and hemocytes are counted in adults [ 46 ]. Therefore, we predict that the surge in hemocytes associated with the initial infection—by the mitosis of circulating hemocytes [ 45 ]—carries over to strengthen the fight against the second infection.…”
Section: Discussionmentioning
confidence: 99%
“…We found a similar inverse correlation when studying cellular immunity in larvae and differently-aged adults; larvae have more hemocytes than adults but a smaller percentage of hemocytes engage in phagocytosis [ 37 ]. This contrasts with mosquitoes that were infected with E. coli as larvae and reinfected with E. coli as adults, where the number of hemocytes in mosquitoes infected twice was higher and so was their phagocytic activity [ 46 ]. This latter finding is similar to the strengthened phagocytosis response observed in mosquitoes treated with 20E [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation